Association of the estrogen receptor gene with oral health-related quality of life in patients with dentofacial deformities - Nilza Cristina MACHADO; Jennifer Tsi GERBER; Katheleen Miranda dos SANTOS; Isabela Polesi BERGAMASCHI; Michelle Nascimento MEGER; Delson João da COSTA; Erika Calvano KÜCHLER; Rafaela SCARIOT (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract This study aimed to evaluate the associations between oral health-related quality of life (OHRQoL) and patient-associated factors and polymorphisms in the estrogen receptor 1 (ESR1) and 2 (ESR2) genes in patients with dentofacial deformities (DFD). This cross-sectional study included 234 adult individuals. Data such as age, sex, and the type of facial profile (I, II, or III), were collected, and the short-form oral health impact profile 14 (OHIP-14) questionnaire was used to assess their OHRQoL. DNA was collected from oral mucosa cells, and the polymorphisms in ESR1 (rs2234693 and rs9340799) and ESR2 (rs1256049 and rs4986938) were evaluated using real-time polymerase chain reaction. The data were subjected to statistical analysis at a significance level of 5%. Individuals over 28 years of age exhibited worse OHRQoL (p = 0.003) than individuals aged less than or equal to 28 years. Women had worse OHRQoL than men (p < 0.001). Profile II individuals had worse OHRQoL in the social disability domain than profile III individuals (p = 0.030). Genetic analysis showed that rs9340799 was associated with OHRQoL in the functional limitation domain, and GG individuals exhibited worse OHRQoL than individuals carrying the AA/AG genotypes (p < 0.030). In the social handicap domain, individuals with GG genotype in rs9340799 exhibited worse OHRQoL than AG individuals (p < 0.043). Collectively, our results reveal that factors including age, sex, and type of facial profile, are associated with OHRQoL in patients with DFD. In addition, individuals with the GG genotype in rs9340799 (ESR1) may experience a negative impact on OHRQoL in the functional limitation and social handicap domains.